Effects of COVID-19 Lockdown on Time in Therapeutic Range (TTR) for Warfarin Users - Aktaş, İbrahim; Sarıoğlu, Güney; Yaşar, Erdoğan (The European Research Journal, 2026)
Objective: This study investigated the impact of COVID-19 lockdown measures on Time in Therapeutic Range (TTR) for patients receiving warfarin therapy. Methods: A retrospective cohort study was conducted at a tertiary care hospital in Malatya. Patients receiving warfarin for at least one year before and after March 11th, 2020 (the start of pandemic) were included (n=112). Demographic data, comorbidities, medications, and International Normalized Ratio (INR) results were collected. TTR was calculated using the Rosendaal method. Results: The mean TTR before the pandemic was 56.91%, significantly higher than the 40.23% observed during the pandemic (P